Gold and pathfinder elements in ferricrete gold deposits of the Yilgarn Craton of Western Australia: A review with new concepts - Anand, R.; Hough, R.; Salama, W.; Aspandiar, Mehrooz; Butt, C.; González-Álvarez, I.; Metelka, V. (Elsevier Science BV, 2019)
Secondary mineral deposits have played an important role in the global mineral resource economy for over 50 years, with lateritic Au, Al, Fe and Ni deposits having a significant input to global metal production and reserves. In the Yilgarn Craton of Western Australia, a deeply weathered mantle is commonly capped with 2–10 m of lateritic residuum (residual lateritic gravels and duricrust) and/or ferricrete (Fe oxide-cemented sediment), which formed under seasonally humid tropical and sub-tropical climates during the Cenozoic. The principal constituents of these units are goethite, hematite, maghemite, kaolinite and quartz. They are commonly overlain by younger, 2–10 m thick transported cover, deposited under later semi-arid conditions. Both ferricrete and lateritic residuum may host exploitable secondary gold deposits, typically small (<500,000 ounces) and of low grade (<1–5 g/t Au). The lateritic residuum deposits overlie weathered and fresh primary mineralization, whereas ferricrete deposits overlie uneconomic primary mieralization or barren saprolite and bedrock. Despite numerous studies, many questions remain about the behaviour and evolution of Au in the complex polygenetic systems that form lateritic residuum and ferricrete. In particular, why is it difficult to locate significant primary mineralization associated with highly Au-anomalous ferricrete? Understanding the mechanisms of enrichment of Au and pathfinder elements in ferricrete will assist future discovery. Accordingly, to obtain conclusive evidence for processes of anomaly formation, a combination of detailed field observations with state-of-the-art microscopy have been conducted at three of the larger deposits (Moolart Well, Mt Gibson and Bulchina). The aim of this review is to integrate these recent results with the results of earlier studies to trace the path of Au and pathfinder elements and associated dispersion processes in the ferricrete environment.